Modal analysis of anisotropic diffused-channel waveguide by a scalar finite element method - Franco, MAR; Passaro, A.; Neto, F. S.; Cardoso, JR; Machado, J. M. (Institute of Electrical and Electronics Engineers (IEEE), 1998)
A procedure to model optical diffused-channel waveguides is presented in this work. The dielectric waveguides present anisotropic refractive indexes which are calculated from the proton concentration. The proton concentration inside the channel is calculated by the anisotropic 2D-linear diffusion equation and converted to the refractive indexes using mathematical relations obtained from experimental data, the arbitrary refractive index profile is modeled by a. nodal expansion in the base functions. The TE and TM-like propagation properties (effective index) and the electromagnetic fields for well-annealed proton-exchanged (APE) LiNbO3 waveguides are computed by the finite element method.
Keywords: finite element methods; nonhomogeneously loaded waveguides; optical strip waveguides; anisotropic media; diffusion processes